أثر برنامج تدريبي مقترح لبعض المهارات الادراكية الحركية على الأداء المهاري للاعبي كرة القدم U17 - كمال, ملوك (Tamayoz, 2019)
تهدف هذه الدراسة الموسومة بعنوان " أثر برنامج تدريبي مقترح في تحسين بعض المهارات الادراكية الحركية لتحسين الأداء المهاري للاعبي كرة القدم U17 إلى معرفة " إلى معرفة الفروق الفردية بين اللاعبين من حيث الاداء المهاري و المهارات الحركية الادراكية، حيث من اجل الوصول إلى نتائج أفضل ونظرا للضرورة العلمية اعتمدنا في هذه الدراسة على المنهج المسحي التجريبي نظرا لملائمته لطبيعة الموضوع المدروس ، و تمت الدراسة على عينة قوامها ( 30 لاعبا ناشئا ) ،قسموا إلى مجموعتين ضابطة و تجريبية و هذا قصد دراسة العلاقات الارتباطية ما بين البرنامج التدريبي المقترح المبني على الألعاب التمهيدية و القدرات الإدراكية الحركية و الأداء المهاري . Abstract : This study, entitled "The effect of a proposed training program in improving some cognitive cognitive skills to improve the skillful performance of U17 football players," aims at identifying the individual differences between players in terms of skill performance and cognitive motor skills. In order to achieve better results and due to the scientific necessity, we adopted in this study the experimental survey method because it is suitable for the nature of the studied subject. The study was conducted on a sample of (30 young people), divided into two experimental and experimental groups, The proposal is based on preliminary games, cognitive abilities and skill performance We have adopted five standardized physical tests and five skill tests as data collection tools from the field, after ascertaining their psychometric properties (honesty, consistency, objectivity), using statistical and descriptive techniques and techniques to transform qualitative data into quantitative data that can be analyzed and measured.